Body mass index associates with white matter microstructure in bipolar depression. (18th April 2017) - Mazza, Elena; Poletti, Sara; Bollettini, Irene; Locatelli, Clara; Falini, Andrea; Colombo, Cristina; Benedetti, Francesco
Abstract : Objectives: Obesity has been reported in over 60% of bipolar disorder (BD) patients. It worsens the severity of illness, and influences cognition and functional outcomes. White matter (WM) abnormalities are one of the most consistently reported findings in neuroimaging studies of BD. We hypothesized that body mass index (BMI) could correlate with WM integrity in bipolar patients. Methods: We evaluated BMI in a sample of 164 depressed patients affected by BD. We performed whole‐brain tract‐based spatial statistics with threshold‐free cluster enhancement for the diffusion tensor imaging (DTI) measures of WM integrity: fractional anisotropy; axial, radial, and mean diffusivity. Results: We observed that BMI was associated with DTI measures of WM integrity in several fiber tracts: anterior corona radiata, anterior thalamic radiation, inferior fronto‐occipital fasciculus and corpus callosum. Conclusions: The association of BMI in key WM tracts that are crucial to mood regulation and neurocognitive functioning suggests that BMI might contribute to the pathophysiology of BD through a detrimental action on structural connectivity in critical cortico‐limbic networks.